The pajama game [videorecording (DVD)] - Abbott, George, 1887-1995; Bissell, Richard, 1913-1977; Donen, Stanley; Fosse, Bob, 1927-1987; Adler, Richard, 1921-2012; Ross, Jerry, 1926-1955; Day, Doris, 1922-2019; Raitt, John, 1917-2005; Haney, Carol; Foy, Eddie, 1905-1983; Shaw, Reta, 1912-1982; Nichols, Barbara, 1929-1976; et al. (Warner Home Video, 1999)
A labor/management dispute at the Sleeptite Pajama Factory is the subject of this musical comedy.